A simple supported tubulated bilayer system for evaluating protein-mediated membrane remodeling. (September 2018) - Schenk, Noah A.; Dahl, Peter J.; Hanna, Michael G.; Audhya, Anjon; Tall, Gregory G.; Knight, Jefferson D.; Anantharam, Arun
Graphical abstract: Highlights: Depositing liposomes under high ionic strength incorporates excess lipids into supported lipid bilayers. Excess lipid is accommodated in the z-direction by lipid tubules, forming S upported Tu bulated B ilayers (STuBs). Pre-formed lipid tubules can be used to measure protein-mediated membrane remodeling in real time easily and quantitatively. The GTPase Sar1B when bound to GTP significantly remodels membranes whereas Sar1B bound to GDP does not. Abstract: Fusion and fission of cellular membranes involve dramatic, protein-mediated changes in membrane curvature. Many of the experimental methods useful for investigating curvature sensing or generation require specialized equipment. We have developed a system based on supported lipid bilayers (SLBs) in which lipid tubules are simple to produce and several types of membrane remodeling events can be readily imaged using widely available instrumentation (e.g., tubule fission and/or membrane budding). Briefly, high ionic strength during lipid bilayer deposition results in incorporation of excess lipids in the SLB. After sequentially washing with water and physiological ionic strength buffer solutions, lipid tubules form spontaneously. We find that tubule formation results from solution-dependent spreading of the SLB; washing from water into physiological ionic strength buffer solution leads to expansion of the bilayer and formation of tubules. Conversely, washing from physiological buffer into water results in contraction of the membrane and loss of tubules. We demonstrate the utility of these supported tubulated bilayers, termed "STuBs, " with an investigation of Sar1B, a small Ras family G-protein known to influence membrane curvature. The addition of Sar1B to STuBs results in dramatic changes in tubule topology and eventual tubule fission. Overall, STuBs are a simple experimental system, useful for monitoring protein-mediated effects on membrane topology in real time, under physiologically relevant conditions.